2020
DOI: 10.3390/ijms21197420
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Survivin and Macrophage Infiltration Quantified on Protein and mRNA Level in Molecular Subtypes Determined by RT-qPCR of KRT5, KRT20, and ERBB2 in Muscle-Invasive Bladder Cancer Treated by Adjuvant Chemotherapy

Abstract: Objectives: Bladder cancer is a heterogeneous malignancy. Therefore, it is difficult to find single predictive markers. Moreover, most studies focus on either the immunohistochemical or molecular assessment of tumor tissues by next-generation sequencing (NGS) or PCR, while a combination of immunohistochemistry (IHC) and PCR for tumor marker assessment might have the strongest impact to predict outcome and select optimal therapies in real-world application. We investigated the role of proliferation survivin/BIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…We showed that intratumoral Clever-1 + macrophages correlated with a better DSS, whereas peritumoral Clever-1 + macrophages did not affect prognosis. Although Clever-1 + macrophages generally have been associated with a worse prognosis [21][22][23][24]26], peritumoral Clever-1 + macrophages have been associated with a better prognosis in colorectal carcinoma in early stage [27]. The location of Clever-1 + macrophages seem to be important as intratumoral, unlike stromal, Clever-1 + macrophages have been associated with a higher grade and stage and worse prognosis in bladder cancer [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that intratumoral Clever-1 + macrophages correlated with a better DSS, whereas peritumoral Clever-1 + macrophages did not affect prognosis. Although Clever-1 + macrophages generally have been associated with a worse prognosis [21][22][23][24]26], peritumoral Clever-1 + macrophages have been associated with a better prognosis in colorectal carcinoma in early stage [27]. The location of Clever-1 + macrophages seem to be important as intratumoral, unlike stromal, Clever-1 + macrophages have been associated with a higher grade and stage and worse prognosis in bladder cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Clever-1 + macrophages have been recorded in solid cancers such as melanoma [19] and glioblastoma [20]. They associate with a worse prognosis in bladder carcinoma [21][22][23] and predict metastasis and risk of recurrence in oral cavity squamous cell carcinoma [24]. Clever-1 + macrophages in gastric cancer predict worse prognosis in tumors with a high T-lymphocyte count [25] or in early stage tumors [26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the presence of survivin in bladder cancer tissue has been consistently documented in several publications [ 22 , 23 ]. Current studies explore survivin as a molecular target for therapy, thereby elucidating whether the subcellular location of survivin may be associated with tumor aggressiveness [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%